2018
DOI: 10.1080/08927936.2018.1482113
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of, and Attitudes toward, Bats in Barak Valley, Assam, India

Abstract: In ecology, foraging requires animals to expend energy in order to obtain resources. The cost of foraging can be reduced through kleptoparasitism, the theft of a resource that another individual has expended effort to acquire. Thus, kleptoparasitism is one of the most significant feeding techniques in ecology. In this study, we investigate a two predator one prey paradigm in which one predator acts as a kleptoparasite and the other as a host. This research considers the post-kleptoparasitism scenario, which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 59 publications
(57 reference statements)
0
13
1
1
Order By: Relevance
“…The habitat loss and fragmentation, and transformation of natural environments may disconnect populations, favoring possible local extinction events (Lino et al 2019). Furthermore, intentional killings at the hands of local people who perceive bats as a threat, as occurs for other species of bats, could be causing the loss of a considerable number of individuals, mainly associated with the lack of knowledge and disinformation of the ecosystem services they provide (O'Shea et al 2016;Bhattacharjee et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The habitat loss and fragmentation, and transformation of natural environments may disconnect populations, favoring possible local extinction events (Lino et al 2019). Furthermore, intentional killings at the hands of local people who perceive bats as a threat, as occurs for other species of bats, could be causing the loss of a considerable number of individuals, mainly associated with the lack of knowledge and disinformation of the ecosystem services they provide (O'Shea et al 2016;Bhattacharjee et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that gender, educational level, religiousness and previous contact with bats were associated with attitudinal dimensions. Regarding gender, females tended to have a more negative attitude than males (Bhattacharjee et al 2018;Lu et al 2021;Musila et al 2018;Prokop & Tunnicliffe 2008;Shapiro et al 2020;Suwannarong et al 2020), probably because bats are often associated with fear-relevant animals, such as rats and mice (Pol ak et al 2020). This is an important factor to be considered in conservation strategies or campaigns, where the information approach should differ according to gender.…”
Section: Discussionmentioning
confidence: 99%
“…With >1400 species (Upham et al 2019), they occupy a great variety of trophic niches, fulfilling numerous functions in maintaining the ecosystems' health (Jones et al 2009) and providing relevant ecosystem services for humans as seed dispersers, pollinators and pest suppressors with substantial impact for the socioeconomic systems (Boyles et al 2011;Kunz et al 2011). However, various studies show that social perception of bats tends to be negative (e.g., Bhattacharjee et al 2018;Kingston 2016;Prokop et al 2009;Reid 2016;Sexton & Stewart 2007). This perception worsened due to the Covid-19 pandemic, in which bats have been implicated as a possible origin (Zhao 2020;Zhou et al 2020), although people misunderstood the relationships between them (Covid-19 and bats) even with a sample of 15 000 Chinese participants (Lu et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In southwest Asia, bat folklore has been documented between Iran, India, and Myanmar [25][26][27]. In southwest Asia, the bat is predominantly perceived as a strange, negative, and demonic animal that should be avoided.…”
Section: Southwest Asiamentioning
confidence: 99%